A quasi-experimental research on developing students’ life skills through purposeful leisure time activities - Koçak, Göknil Nur; Çetin, Mehmet Çağrı; Kara, Mehmet; Genç, Murat; Lekesiz, Gültekin; Açıkbaş, Ferhat Caner; Kara, Nuriye Şeyma (Frontiers in Psychology, 2025)
This study investigated the efficacy of a camp-based intervention in enhancing students’ life skills and subjective wellbeing. This research examined how student-centered and interactive learning models, implemented through camp activities, contributed to the development of participants’ life skills. Using a quasi-experimental methodology with a pretest/post-test control group design (2 × 2 factorial design), the study employed experimental and control conditions to establish validity. Life skills and subjective wellbeing data were collected through face-to-face administration at consistent time points, before and after the intervention. The study involved 46 students assigned to the experimental group and 42 students assigned to the control group, all of whom were enrolled in the Faculty of Sports Sciences. Statistical analysis employed a mixed-design two-way ANOVA to assess between-group differences and temporal changes, while predictive relationships were examined through correlation and regression analyses. The results demonstrated statistically significant positive changes in both life skills and subjective wellbeing measures among experimental participants compared to their control group counterparts who did not participate in the camp intervention. This finding supports the idea that organized camps can serve as catalysts for improving subjective wellbeing and the development of life skills. As anticipated, enhanced life skill development corresponded to increased subjective wellbeing. The study further determined that interactive structures implemented within the camp framework effectively supported both life skills development and subjective wellbeing enhancement. Camp-based interventions may be recommended as effective tools for developing competencies within organizational human resources, including stress management, problem solving, interpersonal communication, decision-making, and creative and critical thinking.